First‐Principles Investigation of Phase Stability in Substoichiometric Zirconium Carbide under High Pressure. Issue 12 (19th August 2022) - Thiel, Scott D.; Walsh, James P. S.
Abstract: NaCl‐type carbides of the early transition metals can exhibit a substantial sub‐stoichiometry at the carbon site, impacting a host of bulk properties that depend upon carbon concentration including melting points, mechanical and elastic properties, and superconducting transition temperatures. Unfortunately, control over vacancies remains challenging with current preparation methods, motivating the search for new synthetic approaches that will allow for the prescription of specific vacancy configurations. Here, density functional theory is augmented with alloy cluster expansion to examine the structure and zero kelvin enthalpy of millions of structures across composition and pressure space. The results are used to examine how extreme pressures might be used to access novel ordered and disordered phases of ZrC, many of which have been calculated to be thermodynamically stable yet remain synthetically elusive. High pressure is shown to significantly reduce sub‐stoichiometry and drive the system toward fully stoichiometric ZrC. They examine the root of these changes and find that pressure exerts an influence over the distribution and abundance of specific nearest‐neighbor vacancy pairs. These results suggest that pressure is a powerful tool for the control of vacancies, and can offer a new synthetic handle on the bulk properties exhibited in this industrially important class of materials. Abstract : Density functional theory is augmented with alloy cluster expansion to examine the structure and zero kelvin enthalpy of millions of structures across composition and pressure space. Results are used to examine how extreme pressures might be used to access novel ordered and disordered phases of ZrC, many of which have been calculated to be thermodynamically stable yet remain synthetically elusive.